The Process of Creating Violence in S.E.A.Write Award-Winning Short Stories - Inkham, Phailin; Kaencandra, Vajrindra; Hemmaratrak, Khongamon; Yingyoungsak, Warunya; Lordee, Sarawut (Journal of Human and Society, Sisaket Rajabhat University, 2025)
This research aims to analyze of creating violence, which portrayed in short stories that have received the S.E.A. Write Award, using Johan Galtung’s (1996) concept of violence and Watcharin Kaenchan’s (2017) as the framework of creating violence as the analytical framework. The findings reveal five main processes through which violence is constructed in these S.E.A. Writing Award works: (1) legitimization, (2) marginalization/othering, (3) devaluation of human dignity, (4) commodification, and (5) identity alteration. Moreover, the study finds that these processes often co-occur. For example, devaluation of human dignity is combined with legitimization, or with marginalization/othering; legitimization is also found alongside marginalization/othering, and with commodification.